2008
DOI: 10.3892/or.20.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Incubation with somatostatin, 5-aza decitabine and trichostatin up-regulates somatostatin receptor expression in prostate cancer cells

Abstract: Somatostatin (SMS), binds to its specific receptors (SSTRs) and transduces growth inhibitory, anti-secretory and apoptotic signals. Several human cancers express SSTRs, including prostate cancer, and therefore SMS is of interest for anti-cancer therapy. DNA methylation and histone modifications are involved in normal cell development, gene imprinting and human carcinogenesis. Reversing DNA methylation is an attractive therapeutic possibility, since epigenetic modifications change gene expression without changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Previous studies suggested effects on a transcriptional level via DNMT and HDAC inhibition (26,27) and on a translational level via HDAC inhibition (28). In the present study, we confirmed these findings and expanded the principle to the functional level in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies suggested effects on a transcriptional level via DNMT and HDAC inhibition (26,27) and on a translational level via HDAC inhibition (28). In the present study, we confirmed these findings and expanded the principle to the functional level in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…The medium was changed two times a week and the cells were trypsinized and subcultivated once a week. Smsdx was prepared as described previously (5). Sms was from Ferring, Kiel, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…51 Comparable effects have been recently observed in prostate cancer cells, in which DAC exposure increased the efficacy of treatment with the growth inhibitor somatostatin by inducing the upregulation of its receptor. 52 Similarly, AZA and DAC have been successfully exploited in solid cancers to enhance tumor immunogenicity. Aberrant expression of recognition antigens, one of the main mechanisms used by cancer cells to evade the host immune system, is frequently imputable to promoter hypermethylation of the corresponding genes.…”
mentioning
confidence: 99%